Rare‐Earth Substitution Induced Symmetry Breaking for The First Sc‐Based Nonlinear Optical Chalcogenide with High‐Performance - Chen‐Yi Zhao; Chun‐Li Hu; Nian‐Tzu Suen; Xiao‐Hui Li; Hai‐Ping Xu; Wenfeng Zhou; Sheng‐Ping Guo (Advanced Science)
Abstract Chalcogenides are the most important infrared nonlinear optical (NLO) material candidates, and the exploration of high‐performance ones is attractive and challengeable. Hitherto, there is no NLO scandium (Sc) chalcogenides experimentally studied. Here, new quaternary Sc thiophosphate CsScP2S7 (CSPS) was synthesized by the facile metal oxide‐boron‐sulfur/reactive flux hybrid solid‐state method. It crystallizes in the monoclinic chiral space group C2, and the layered structure is composed by the new ScP2S11 functional motifs built by ScS6 octahedra and P2S7 dimers, and the structure‐performance analysis reveals that the hyperpolarizability of ScP2S11 is much greater than the assembled units (ScS6 and PS4), which makes the first NLO Sc chalcogenide CSPS exhibits strong NLO response (0.8 × AGS) and high laser‐induced damage threshold (LIDT) (4.3 × AGS), and a wide bandgap of 3.10 eV. With the coordination number's reduction of rare‐earth (RE) ion and the rearrangement of P2S7 dimers, the centrosymmetric structure of CsREP2S7 family can be broken via substitution with the smallest RE element Sc to form the noncentrosymmetric structure. This work not only discovers a new high‐performance infrared NLO material, but also will inspire researchers to explore more potential NLO Sc chalcogenides.